HUBUNGAN ANTARA ADEKUASI HEMODIALISIS DENGAN KUALITAS HIDUP PASIEN HEMODIALISIS DI UNIT HD RUMAH SAKIT UMUM ROYAL PRIMA MEDAN - Siahaan, Juwita Verawati (Universitas Prima Indonesia, 2018)
Hemodialysis is a dialysis theraphy most widely performed that is 2-3 times a week in 4-5 hours, which aims to remove the remnants of the metabolism of proteins and correct fluid and electrolyte balance disorders. Based on estimates made by the World Health Organization (WHO), globally more than 500 million people have chronic renal failure. About 1.5 million people have to live dependently on dialysis. This study was conducted to determine the relationship between adequacy for hemodialysis with the quality of life for hemodialysis patients at HD unit in Royal Prima Hospital Medan. This type of research is analytic descriptive with cross sectional study design. The samples of this study were all patients who underwent therapy in hemodialysis unit at Royal Prima Hospital Medan in December consisting of 29 patients. Based on the results of the chi-square test on the relationship between hemodialysis adequacy and quality of life for hemodialysis patients at HD uint in Royal Prima Hospital Medan with a significance level (α) = 0.05 and df = 1 it was obtained that calculation results was p (0.000) <0, 05, then Ho is rejected and Ha is accepted. In conclusion there is a relationship between hemodialysis adequacy and quality of life of patients on hemodialysis at HD unit of the Royal Prima Hospital Medan. In conclusion, There is a relationship between hemodialysis adequacy and quality of life for hemodialysis patients at HD unit in Royal Prima Hospital Medan. It is expected that the Royal Prima Hospital Medan can improve service policy at HD unit to perform hemodialysis for 5-6 hours. This should be performed so that the adequacy of the achievement can be optimized so quality of life expected by respondents can be increased.